Nurse-led lifestyle counseling in Polish primary care: the effect of current health status and perceived barriers - Znyk, Małgorzata; Kostrzewski, Szymon; Kaleta, Dorota (Frontiers in Public Health, 2024)
Our study included counseling on diet and physical activity, smoking, e-cigarette use, and alcohol consumption. The aim was to examine the correlates of counseling provided by primary care nurses with the health status/ health behaviors of nurses and the barriers in the advice provided.In 2022, we conducted a cross-sectional survey among 331 nurses employed in the primary care sector in Lodz. The questionnaire consisted of three sections: characteristics of the patient population receiving treatment and provided with healthy lifestyle counseling by nurses, barriers to the process of assessing, controlling, and guiding patients, and health status/health behaviors of nurses.Results: Eighty percent of the nurses in our study provided advice on diet and physical activity to primary care patients. Over 70% of the survey participants performed minimal anti-smoking interventions forsmokers, 67.7% for alcohol drinkers, and 56.8% for e-cigarette users. The correlates of counseling in the field of diet and physical activity turned out to be the knowledge and skills which enabled nurses to provide advice (OR=2.57, p<0.01). The correlates of the conducted minimal anti-smoking interventions in smoking patients were: subjective assessment of overweight and obesity in nurses, knowledge and skills in conducting counseling (OR=1.92, p<0.05), and measuring body weight, height and BMI (OR=2.18, p<0.01). Among the three most common barriers identified by the nurses in the process of assessing, monitoring, and guiding patients were the opinion that patients are not interested in improving their diet, physical activity, and weight loss (60.7%), lack of time (51.4%), as well as the belief that patients find it too difficult to change their current habits (54.1%).The results of our survey indicate that nurses' participation in healthy lifestyle counseling in adult patients is unsatisfactory. Interventions in primary care should be designed considering the specific obstacles nurses may face in leading healthy lifestyles. Further training of nursing staff is required to increase their knowledge on healthy lifestyles.